The Control of a Plasticating Extruder with Flight Noise and Pressure Surging - Costin, Henry Mark (My University, 1981)
Dynamic models for a plasticating extruder melt pressure are formed from steady state, step test and time series analysis data. The extruder pressure response to steps in screw speed is modelled by a first order transfer function with a time constant of approximately 0.2 s. The noise associated with the extruder pressure consists of a pressure surging at 0.125 Hz frequency and a longer term drift associated with the die temperature controller. This drift has a period of approximately 3.0 min. The pressure also has a signal noise at the same frequency as the screw rotation caused by the screw flight passing the tip of the pressure transducer.
The digital PI and the self-tuning regulator control algorithms are used to control the extruder. These controllers are implemented in combination with various filters which remove the flight noise. The most successful controller/filter combination is a digital PI controller used with a filter constructed from 2 poles and 2 zeroes.
The dynamic response of a disturbance caused by changing the input polymer quality is also examined. The use of Box and Jenkins seasonal time series models as bandstop filters is studied and it is concluded that they have little practicality as filters. Another topic covered by the thesis is the effect that including filters in the forward transfer function part of a process has on the self-tuning regulator algorithm.
Keywords: Chemical Engineering; Chemical Engineering